Factors associated with low bone mineral density in Turner syndrome: a multicenter prospective observational study - Kento Ikegawa; Eri Koga; Tomoyo Itonaga; Hideya Sakakibara; Masanobu Kawai; Yukihiro Hasegawa (Endocrine Journal)
Turner syndrome (TS) is associated with a high risk of fracture due to low bone mineral density (BMD). While hypogonadism is known to play a role in decreasing BMD, other factors have not been studied well. Focusing on diet, exercise, and bone metabolism markers, the present, multicentric, prospective, observational study aimed to identify factors contributing to decreased BMD in TS. In total, 48 patients with TS aged between 5 and 49 years comprising a pre-pubertal group (n = 9), a cyclical menstruation group (n = 6), and a hormone replacement therapy (HRT) group (n = 33) were enrolled. The cyclical menstruation group and the HRT group were referred to collectively as the post-pubertal group. The bone mineral apparent density (BMAD) Z-score was higher in the pre-pubertal group than in the post-pubertal group (–0.3 SD vs. –1.8 SD; p = 0.014). Within the post-pubertal group, the median BMAD Z-score was –0.2 SD in the cyclical menstruation group and –2.3 SD in the HRT group (p = 0.016). Spearman’s rank correlation revealed no correlation between the BMAD Z-score and bone metabolism markers. No significant relationship was observed between the BMAD Z-score and either the vitamin D sufficiency rate or the step sufficiency rate. A negative correlation was found between BMAD Z-score and serum sclerostin in the pre-pubertal group and serum FSH in the post-pubertal group. In conclusion, the present study found no relationship between the vertebral BMAD Z-score and diet or exercise habits in TS, indicating that estrogen deficiency is the chief reason for low BMD in TS.